225Aс-PSMA-617 therapy in metastatic castration-resistant prostate cancer - T. Yu. Kochetova; V. V. Krylov; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал)
177Lu-PSMA-617 is a new therapy option for PSMA-positive metastatic castrate-resistant metastatic prostate cancer (mCRPC) with proven efficacy. 225Ac-PCMA-617 is an alpha emitter, making this drug potentially more powerful. Despite the active use of 225Ac-PSMA-617 worldwide, no randomized phase III studies have yet been conducted. The present prospective cohort study presents the experience of 225Ac-PSMA-617 use in the A.F. Tsyb MRRC. Material and Methods. the study included mCRPC patients with prostate-specific membrane antigen (PSMA) overexpression confirmed by PET-CT or SPECT-CT, who received the first course of therapy in 2023. Results. Forty three patients received 1 to 6 (median 2) administrations of 225Ac-PSMA-617, 26 (60 %) of these patients had a history of 177Lu-PSMA-617 therapy, 13 (30 %) had a history of radium chloride [223Ra] therapy, and 10 (23 %) patients had no history of chemotherapy. Five (12 %) had liver metastases at the time of inclusion in the study. PSA reduction of more than 50 % was recorded in 55 % of patients, with biochemical response significantly more frequent in the PSMA-naïve group, 63 % vs 35 %; the number of adverse events was also lower in this group. But no advantage in overall survival (OS) in PSMA-naïve patients was revealed at the present time. Favorable prognosis factors included a history of radium chloride [223Ra] therapy; in contrast, liver metastasis was a negative prognostic factor. the study found no differences in OS among taxane-naïve patients and patients with a history of 1–2 lines of chemotherapy. Continued therapy with androgen receptor targeted agents after initiation of 225Ac-PSMA-617 treatment also showed no effect on OS. Conclusions. 225Ac-PCMA-617 may be effective in 177Lu-PCMa resistance, but there are no data on the increase in overall patient survival when 225Ac-PCMA-617 is administered as first-line radioligand therapy.